STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH NASABAH TABUNGAN HAJI PADA PT. BANK SUMUT SYARIAH KCP PANYABUNGAN - Anggina Putri; Arwin; Azizatur Rahmah (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study aims to analyze the marketing strategies implemented by PT Bank Sumut Syariah, Panyabungan Branch, in increasing the number of Hajj savings customers. The background of this research is based on the importance of the role of Islamic banking in facilitating the community to perform the Hajj pilgrimage through savings products that comply with Sharia principles. The research method used is a qualitative method with a descriptive approach, and data were collected through interviews, observation, and documentation.The results of the study indicate that the marketing strategies implemented include direct approaches to the community through visits to religious gatherings (majelis) and offices, distributing brochures, collaborating with the local Ministry of Religious Affairs office, promoting through social media, providing free large-scale Hajj rehearsal (manasik haji akbar) in Medan, and delivering fast and friendly service. In addition, the bank also provides education regarding the benefits of Hajj savings and the Sharia-compliant registration procedures. These strategies have proven effective in increasing public awareness and interest in becoming Hajj savings customers.The study concludes that the marketing approach is carried out through a marketing mix (7P) strategy, which includes. Product Goods or services offered to customers. Price Pricing strategies that take into account the purchasing power of the target market. Place Locations and distribution channels that make it easier for customers to obtain products/services. Promotion Activities to introduce and persuade customers, such as advertisements.